A sorghum NAC gene is associated with variation in biomass properties and yield potential. (23rd July 2018) - Xia, Jingnu; Zhao, Yunjun; Burks, Payne; Pauly, Markus; Brown, Patrick J.
Abstract: Sorghum bicolor is a C4 grass widely cultivated for grain, forage, sugar, and biomass. The sorghum Dry Stalk (D) locus controls a qualitative difference between juicy green (dd) and dry white (D‐) stalks and midribs, and co‐localizes with a quantitative trait locus for sugar yield. Here, we apply fine‐mapping and genome‐wide association study (GWAS) to identify a candidate gene underlying D, and use nearly isogenic lines (NILs) to characterize the transcriptional, compositional, and agronomic effects of variation at the D locus. The D locus was fine‐mapped to a 36 kb interval containing four genes. One of these genes is a NAC transcription factor that contains a stop codon in the NAC domain in the recessive (dd) parent. Allelic variation at D affects grain yield, sugar yield, and biomass composition in NILs. Green midrib ( dd) NILs show reductions in lignin in stalk tissue and produce higher sugar and grain yields under well‐watered field conditions. Increased yield potential in dd NILs is associated with increased stalk mass and moisture, higher biomass digestibility, and an extended period of grain filling. Transcriptome profiling of midrib tissue at the 4–6 leaf stages, when NILs first become phenotypically distinct, reveals that dd NILs have increased expression of a miniature zinc finger (MIF) gene. MIF genes dimerize with and suppress zinc finger homeodomain (ZF‐HD) transcription factors, and a ZF‐HD gene is associated with midrib color variation in a GWAS analysis across 1, 694 diverse sorghum inbreds. A premature stop codon in a NAC gene is the most likely candidate polymorphism underlying the sorghum D locus. More detailed understanding of the sorghum D locus could help improve agronomic potential in cereals.